2021
DOI: 10.1128/jvi.02234-20
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum-Associated Degradation Controls Virus Protein Homeostasis, Which Is Required for Flavivirus Propagation

Abstract: Many positive-stranded RNA viruses encode polyproteins and viral proteins are generated by processing the polyproteins. This system produces an equal amount of each viral protein, though their required amounts are different. In this study, we found that the extra membrane-anchored non-structural (NS) proteins of Japanese encephalitis virus and dengue virus are rapidly and selectively degraded by the endoplasmic reticulum-associated degradation (ERAD) pathway. Our gene targeting study revealed that ERAD involvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 44 publications
3
20
0
Order By: Relevance
“…Hence, the cells infected with the virus for 2 h were treated with specific small-molecule VCP ATPase inhibitors, such as DBeQ (26), for 4 h. Treatment with the VCP ATPase inhibitors impaired the production of infectious JEV in the supernatant (Fig. 3C), which was consistent with the results of a previous study (13). A 4-h pulse treatment with DBeQ just after virus inoculation was sufficient to reduce the viral titers.…”
Section: Npl4-vcp Complex Is Required At Early Stage In Viral Life Cyclesupporting
confidence: 89%
See 4 more Smart Citations
“…Hence, the cells infected with the virus for 2 h were treated with specific small-molecule VCP ATPase inhibitors, such as DBeQ (26), for 4 h. Treatment with the VCP ATPase inhibitors impaired the production of infectious JEV in the supernatant (Fig. 3C), which was consistent with the results of a previous study (13). A 4-h pulse treatment with DBeQ just after virus inoculation was sufficient to reduce the viral titers.…”
Section: Npl4-vcp Complex Is Required At Early Stage In Viral Life Cyclesupporting
confidence: 89%
“…Previously, proteome analysis revealed that both NPL4 and VCP co-precipitated with JEV NS4B and DENV NS4B (13). Hence, these interactions were confirmed using the reciprocal pull-down assay.…”
Section: Flavivirus Ns4b Interacts With Npl4-vcp Complexmentioning
confidence: 73%
See 3 more Smart Citations